Pharmacokinetic drug evaluation of rifaximin for treatment of diarrhea-predominant irritable bowel syndrome. (3rd July 2018) - Bruzzese, Eugenia; Pesce, Marcella; Sarnelli, Giovanni; Guarino, Alfredo
ABSTRACT: Introduction : Rifaximin is a poorly absorbable antibiotic with a broad-spectrum activity against both Gram-negative and -positive bacteria. It is active in the small intestine due to its high bile solubility, whereas in the aqueous environment of the colon, it shows limited efficacy against highly susceptible bacteria. These unique pharmacokinetic properties limit its systemic effects and can correct gut microflora imbalances. Thus, rifaximin has become a major therapeutic agent in several gastrointestinal diseases in which an imbalance in gut microflora may play a role, including diarrhea predominant irritable bowel syndrome (IBS-D). Area covered : This is an up-to-date review focusing on the efficacy of rifaximin in the treatment of IBS-D in both adult and pediatric populations. We will review the pharmacokinetic properties of rifaximin, including its absorption in health and disease, mechanisms of action, and interactions with other drugs. Expert opinion : Given its safety profile and its negligible absorption, rifaximin is a suitable treatment for IBS-D, in both adults and children. The possibility of modulating gut microbiota composition without side effects has made this drug an appealing therapeutic agent in highly prevalent gastrointestinal diseases. However, to date, monitoring for the development of resistant bacterial strains during long-term rifaximin use is still lacking.